The physiology of flowering plants : their growth and development - Street, H. E.; Opik, Helgi, 1936- (London : Edward Arnold, 1976)
The Physiology of Flowering Plants provides a modern and comprehensive treatment of the developmental aspects of plant physiology. Throughout the book emphasis is placed on the development and testing of theoretical concepts by reference to the critical experimental work. This new edition treats plant water relations in universal terminology, and incorporates new material from the most active fields of current research. These include the metabolism of germination, the transpon of organic solutes, stress physiology, geotropism, cytodifferentiation and morphogenesis. As with all experimental studies in the book, the use of new culture techniques in studies on vegetative and reproductive development is emphasized and illustrated by specially prepared photographs and diagrams. Carefully chosen lists of Further Reading enable the advanced student to further develop his understanding of each of the major fields discussed. All scientific terms and mathematical and chemical expressions are carefully explained.
Incluye referencias bibliográficas
Keywords: CRECIMIENTO (PLANTAS); DIFERENCIACION CELULAR; FISIOLOGIA VEGETAL